Making confident and competent readers of Cell, Nature and Science papers using a flipped classroom approach to introduce protein detection techniques - de Vries, Teun J. (Frontiers in Education, 2023)
It is beneficial for all biomedical track courses to train students early in their educational career in reading biomedical literature. A shortcoming of many biomed track courses during undergraduate education is that laboratory techniques necessary for fully understanding further reading of biomedical articles are not part of courses early in the curriculum. To bridge this gap, an educational investment is needed that will create confident and competent readers of scientific biomedical literature. All consecutive courses in the biomedical track may benefit from such an investment. Probably, the nescience of techniques needed for protein detection, which are part of virtually all composite figures in cell biological articles, forms the basis of such a gap. Activating forms of education were shown to be effective and are increasingly implemented in higher education. Here, the implementation of a flipped classroom approach for explaining ELISA, Immunohistochemistry, Western Blotting and flow cytometry as four common basic protein detection methods is described. The successfulness of the educational approach was assessed in the exam, where a comparison was made between the experts’ and receivers’ grades. Students gave feedback on whether this method made them more confident and competent readers of biomedical literature. Experts on the four techniques were successful in conveying their field of expertise since exam performances on the specific techniques were equally good between experts and receivers. The flipped classroom activity made students more confident (65% agreed vs 18% disagreed) and more competent (79% agreed vs 12% disagreed). Interpretation of research data is only possible when knowing the ins-and-outs of the techniques used to achieve those. Knowledge of protein detection techniques and subsequent confidence and competence in reading scientific biomedical literature gained early in the curriculum is crucial for later courses in the biomedical track.